Facile preparation of reduced graphene oxide/polypyrrole nanocomposites with urchin-like microstructure for wide-potential-window supercapacitors. (1st November 2018) - Han, Yongqin; Zhang, Zonglin; Yang, Mei; Li, Tingxi; Wang, Yanmin; Cao, Aiping; Chen, Zhongxing
Abstract: Reduced graphene oxide (RGO)/polypyrrole (PPy) nanocomposites (GPs) with urchin-like and well-defined doping structure are synthesized by a very facile one-step method. The redox-active 1, 4-benzoquinone, embedded in graphene oxide (GO) sheets, can be "in situ" served as both oxidant of PPy and its reduced state-hydroquinone used as the reductant of GO. One-dimensional nanowire-like PPys assembling on the two-dimensional RGO sheets formed three-dimensional urchin-like porous microstructure. The doping structure of the GPs can also be confirmed by N1s of X-ray photoelectron spectrometer results. As a result, the GPs provided dramatically improved specific capacitances as well as wider potential window compared with pristine GO and PPy. GP3 (the weight percentage of GO is 30 wt%) and GP5 (the weight percentage of GO is 50 wt%) supercapacitor devices also demonstrated high energy density as well as good cycling stability.